Korelasi Tradisi, Kelentukan Dan Kelincahan Dengan Keterampilan Bermain Sepakbola Pada Siswa Sekolah Sepakbola Putra Kutablang (SSB) Kabupaten Bireuen - Hidayat, Rahmad; Fadhil, Imran; Saputra, Dedi; Rohadatul 'Alsy; Rosyidah, Isy Maryam (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2024)
The ability to play soccer is influenced by psychological factors of physiological factors. Physiological factors are physical conditions which in this case are flexibility and agility while psychology in which there are aspects of tradition. This study aims to determine the contribution of tradition, flexibility and agility with the ability to play soccer Putra Kutablang Bireun Regency. The population in this study were all Kutablang Putra Students of Bireun Regency totaling 33 people. Based on the sampling reference with the total sample method, all Kutablang Boys of Bireun Regency are sampled. From the results of data analysis that can be obtained, the correlation coefficient of Tradition (X1) with the ability to play Football (Y) is 0.62, with r count> r table (0.62> 0.291), so there is a correlation of X1 with Y. The coefficient of Determination (X2) with the Ability to Play Football (Y) is 0.54, with r count> r table (0.54> 0.291), so there is a correlation of X2 with Y. The correlation coefficient of Agility (X3) with the Ability to Play Football (Y) is 0.46, with r count> r table (0.46> 0.291), so there is a correlation between X3 with Y. The correlation coefficient together Tradition, Determination, Agility with the Ability to Play Football Putra Kutablang Bireuen amounted to 0.93, For the level of confidence 0.05 and n = 33, with r table = 0.291 and r count = 0.93 it can be concluded that r count> r table (0.93> 0.291). So that there is a correlation of Tradition, Determination and Agility with the Ability to Play Football Putra Kutablang Bireuen. From the calculation of hypothesis testing obtained f count = 62.61 while then obtained the value of f table = 2.94 which means f count = 62.61> from the value of f table, = 2.94 (f count greater than f table,). This means that the hypothesis that the author proposes is accepted.